A Comparative Analysis of Innovation Ecosystems in the EU, the USA, and China - Krushkina, Paolina (Research Papers, 2025)
The study presents a comparative analysis of the innovation models of the European Union, the United States, and China, viewed as three distinct types of innovation ecosystems – value-based, market-oriented, and state-coordinated. The analysis is structured around three main dimensions: (1) institutional and regulatory framework; (2) innovation performance and entrepreneurial dynamics; and (3) the role of intelligent technologies and artificial intelligence. The findings show that the European Union applies a value-based governance model combining ethics, sustainability, and social responsibility; the USA follows a decentralized, market-oriented model driven by entrepreneurial culture and venture capital; while China implements a state-coordinated model in which innovation is integrated into national strategic planning and technological sovereignty. The comparison outlines the specific strengths and limitations of each model, as well as the different balances between innovation, regulation, and state intervention that shape the competitive visions of the EU, the USA, and China for future technological development.
Keywords: Innovations; Innovation ecosystem; European union; USA; China